Changes in DNA bending and flexing due to tethered cations detected by fluorescence resonance energy transfer - Williams, Sarah L. (Oxford University Press, 2006)
Local DNA deformation arises from an interplay among sequence-related base stacking, intrastrand phosphate repulsion, and counterion and water distribution, which is further complicated by the approach and binding of a protein. The role of electrostatics in this complex chemistry was investigated using tethered cationic groups that mimic proximate side chains. A DNA duplex was modified with one or two centrally located deoxyuracils substituted at the 5-position with either a flexible 3-aminopropyl group or a rigid 3-aminopropyn-1-yl group. End-to-end helical distances and duplex flexibility were obtained from measurements of the time-resolved Förster resonance energy transfer between 5′- and 3′-linked dye pairs. A novel analysis utilized the first and second moments of the G(t) function, which encompasses only the energy transfer process. Duplex flexibility is altered by the presence of even a single positive charge. In contrast, the mean 5′–3′ distance is significantly altered by the introduction of two adjacently tethered cations into the double helix but not by a single cation: two adjacent aminopropyl groups decrease the 5′–3′ distance while neighboring aminopropynyl groups lengthen the helix.